The Samaritan Pentateuch an introduction to its origin, history, and significance for biblical studies - Anderson, Robert T., 1928-; Giles, Terry (Atlanta : Society of Biblical Literature, 2012)
"The Samaritan Pentateuch (SP) is the sacred scripture of the Samaritans, a tenacious religious community made famous by Jesus' Good Samaritan story that persists to this day. Not so widely known is the impact of the SP outside the Samaritan community. Recently there has been a resurgence of interest in this scripture, as evidenced by several translations of the SP as well as reference in Qumran scroll studies to the SP or an SP-like tradition in an effort to describe some of the textual evidence present in the scrolls. This volume presents a general introduction to and overview of the SP, suitable for a course text and as a reference tool for the professional scholar"--Back cover.
Includes bibliographical references (p. 195-211) and indexes.
Description based on print version record.
Keywords: Bible. -- Criticism, interpretation, etc; Samaritan literature -- History and criticism; RELIGION / Biblical Studies / Old Testament; Electronic books